Viral vector and nucleic acid vaccines against COVID-19: A narrative review - Khoshnood, Saeed; Ghanavati, Roya; Shirani, Maryam; Ghahramanpour, Hossein; Sholeh, Mohammad; Shariati, Aref; Sadeghifard, Nourkhoda; Heidary, Mohsen (Frontiers in Microbiology, 2022)
After about two years since the first detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in Wuhan, China, in ‎December 2019 that resulted in a worldwide pandemic, 6.2 million deaths have been recorded. As a result, ‎there is an urgent need for the development of a safe and effective vaccine for coronavirus disease 2019 (COVID-19). ‎Endeavors for the production of effective vaccines inexhaustibly are continuing. At present ‎according to the World Health Organization (WHO) COVID-19 vaccine tracker and landscape, 153 vaccine candidates are developing in the clinical phase all over the ‎world. Some new and exciting platforms are nucleic acid-based vaccines ‎such as Pfizer Biontech and Moderna vaccines consisting of a messenger RNA (mRNA) encoding a viral spike protein in host cells. Another novel vaccine platform is viral vector vaccine candidates that could be replicating or nonreplicating. These types of vaccines that have a harmless viral vector ‎like adenovirus contain a genome encoding the spike protein of SARS-CoV-2, which induces significant immune responses. This technology of vaccine manufacturing has previously been used in many human clinical trials conducted for adenoviral vector-based vaccines against different ‎infectious agents, including Ebola virus, Zika virus, HIV, and malaria‎. In this paper, we have a review of nucleic acid-based vaccines that ‎are passing their phase 3 and 4 clinical trials and discuss their efficiency and adverse effects.